Bar Facial Soap Formulation Based on Lerak Fruit Extract (Sapindus rarak DC.) and Aloe Vera Extract (Aloe vera L.) - Yudistira, Liana Oktavianti; Atmanto, Dwi; Jubaedah, Lilis (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Commercial facial cleansers generally use synthetic surfactants such as SLS, which can potentially irritate the skin and damage the skin barrier if used in excessive concentrations and for long periods. This study aims to produce a facial bar soap formulation based on soapberry (Sapindus rarak DC.) and aloe vera (Aloe vera L.) extracts with the best quality, and to analyze its quality characteristics based on SNI 3532:2021. The study used a descriptive quantitative laboratory experiment method with three formulations, namely F0 (control without extract), F1 (5% soapberry extract and 8% aloe vera extract), and F2 (10% soapberry extract and 8% aloe vera extract), which were made using the cold process method. The parameters tested included pH, foam stability, organoleptic, moisture, and antibacterial activity against Staphylococcus aureus. The results showed that all three formulas met the pH and foam stability requirements of SNI 3532:2021. F1 obtained the highest organoleptic value (4.33) and the most standard pH (9.36), while F2 excelled in foam stability (70.00%), increased skin moisture (53.75%), and antibacterial activity with a strong inhibition zone (11.43 mm). The diameter of the inhibition zone increased with increasing concentration of soapberry extract, from moderate (F0) to strong (F1 and F2). Overall, F2 can be considered as the best quality formulation because it excels in three of the five test parameters. The addition of soapberry and aloe vera extracts has been proven to improve the physical and functional quality of bar facial soap compared to the control formula, so it has the potential to be developed as a natural active ingredient in facial soap preparations.